Analisis Linguistik Frasa Roh Kudus dalam Rumusan Trinitas: Bapa, Anak, dan Roh Kudus - Nelwan, Reinhard Mauritz; Hendriks, Alvyn Cesarianto (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study analyses the phrase ‘Holy Spirit’ in the formulation of the Trinity (‘Father, Son, and Holy Spirit’) through a linguistic approach, especially semantics and pragmatics, by referring to the New Testament texts. The research method used is qualitative with a literature observation strategy using the theory of Linguistic Purism. The study results indicate that the term 'Holy Spirit' (Ἁγίoυ Πνεύματος) is neuter-gendered (Greek) or feminine-masculine (Hebrew), unlike other terms denoting the Godhead, which are exclusively male. The use of the neuter pronoun (αὐτό) in John 14:17 and the depiction of the Spirit as part of Christ (Revelation 5:6) reinforce that the Holy Spirit is not distinct, but rather a manifestation of the Spirit of God/Christ. The Trinitarian clause in 1 John 5:7 is not found in pre-16th century manuscripts, suggesting it is an interpolation to support the doctrine of the Trinity. The statement of the Trinity in Matthew 28:19 is regarded as a potential post-Nicene insertion, given that New Testament baptisms only invoke the name of Jesus (Acts 2:38; 19:5). Nonetheless, even if the verse holds validity, the constative concept within Illocutionary Acts elucidates pragmatically that the Holy Spirit is not the third person of the Trinity, but rather the Spirit of God or the Spirit of Christ Himself. This discovery differs from conventional interpretations and presents a more linguistic viewpoint, which is not used as the basic foundation for the formation of the doctrine of the Trinity in Christianity.